(3OQGSI JMdjdjI TGedI dCMcGe GdQgf h GdJCejf h GdGeJjGRs - (3GdbGVj MSjf YHO GddWja(B, (3MeOGfs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2009)
(3Mbhb GdQgf (B: (3JYQja GdQgf h HjGf NUGFUg , EfTGA GdQgf , BKGQ GdQgf , EfbVGA GdQgf , GdGMcGe GdNGUI HCfhGY GdQgf , GdGMcGe GdNGUI HGdQgf GdYbGQj , GdGMcGe GdNGUI HQgf Gdefbhd GdeGOj , MGdGJ NGUI aj Qgf Gdefbhd Mbhb GdJCejf (B:(3GdGMcGe GdYGeI JYQja GdJCejf h HjGf NUGFUg , GdCehGd GdbGHdI ddJCejf , GdehLH GdeVehf HGdJCejf , JSLjd GdJCejf , ehGfY GdJSLjd , CfhGY GdJCejf (B: (3GdJCejfGJ GdQVGFjI , GdJCejfGJ GdELHGQjI , eaGYjd GdJCejf (B: (3eaGYjd GdJCejf HGdfSHI ddOGFf h HGdfSHI ddeDef , EfbVGA GdJCejf (B: (3EfbVGA GdJCejf HUhQI JHYjI h HUhQI CUdjI , JQbjf GdJCejf , Mbhb GdGeJjGR (B: (3GdGMcGe GdYGeI dMbhb GdGeJjGR , GdGMcGe GdNGUI HCfhGY GdMbhb GdeeJGRI (B: (3CMcGe GdGeJjGRGJ GdYGeI , CMcGe GdGeJjGRGJ GdNGUI GdhGbYI Ydi efbhd h GdhGbYI Ydi YbGQs
(3eQGLY U(B.15s
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdQgfs; (3GdbGfhf GdJLGQjs